Monolithically Integrated and Galvanically Isolated GaN Gate Driver - Michael Basler; Richard Reiner; Daniel Grieshaber; Fouad Benkhelifa; Stefan Monch (IEEE Open Journal of Power Electronics)
In this work, a novel monolithically integrated and galvanically isolated GaN gate driver is presented, which combines the separated power and data link of conventional Si-based solutions. The core is an integrated spiral transformer, which is driven on the primary side by a VHF class-D oscillator with on-off keying modulated by the PWM signal. On the secondary side, the signal is rectified and a network ensures the correct off-state. The driver was operated with PWM signals of up to 2 MHz with only one supply voltage of 8 V on the primary side. This GaN IC shows the potential to be integrated with the power transistor in the future to provide a highly compact isolated driver solution on chip.